2021
DOI: 10.1101/2021.02.18.21251442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visuospatial processing impairment following mild COVID-19

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 infection causes coronavirus disease 2019. COVID-19 was an unknown infection that reached pandemic proportions in 2020 and has shown to bring long-term negative consequences. Here, we used a case-control design to investigate the performance of relatively young people recovered from COVID 19 in objective neuropsychological tests. We found significant differences between groups for all measures of the ROCFT with a large difference in the copy, a moderate differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Individuals who recovered from suspected or confirmed COVID-19 had a worse performance on cognitive tests in multiple domains when matched with non-COVID-19 subjects, showing evident deficits even amongst those without severe disease [18]. In a preliminary study, we demonstrated important deficits in the visuospatial processing in around 25% of mild (not requiring hospitalization) COVID-19 patients [19]. Here, we report results of the baseline of a prospective observational cohort study of individuals with mild COVID-19 cases.…”
Section: Introductionmentioning
confidence: 68%
“…Individuals who recovered from suspected or confirmed COVID-19 had a worse performance on cognitive tests in multiple domains when matched with non-COVID-19 subjects, showing evident deficits even amongst those without severe disease [18]. In a preliminary study, we demonstrated important deficits in the visuospatial processing in around 25% of mild (not requiring hospitalization) COVID-19 patients [19]. Here, we report results of the baseline of a prospective observational cohort study of individuals with mild COVID-19 cases.…”
Section: Introductionmentioning
confidence: 68%
“…COVID-19 is a mild to moderate and self-limited illness in most cases and it is caused by severe acute respiratory syndrome coronavirus-2 (SARS-COV-2), a novel coronavirus (1,2). Currently, more than 755 million confirmed cases are reported by WHO worldwide (3).…”
Section: Introductionmentioning
confidence: 99%
“…[24] investigated individuals who recovered from suspected or confirmed COVID-19 and showed these patients had a worse performance on cognitive tests in multiple domains when matched with non-COVID-19 subjects, showing evident deficits even amongst those without severe disease [24]. In a preliminary study, we demonstrated important deficits in the visuospatial processing in around 25% of mild (not requiring hospitalization) COVID-19 patients [25]. Here, we report results of a prospective observational cohort study of individuals with mild COVID-19 cases.…”
Section: Introductionmentioning
confidence: 99%